Analisis kemampuan komunikasi matematis siswa kelas IV pada materi pecahan SD Negeri 4 Simpang Teritip - Pratama , Ananda Wahyu; Trisniawati, Trisniawati; Muanifah, Mahmudah Titi (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study is to describe the mathematical communication skills of grade IV students of SDN 4 Simpang Titip to work on fractional load problems. This study is a quantitative descriptive study in which researchers first conduct instrumental validity and reliability tests before analyzing the data. The subjects of the study were 20 grade IV students of SDN 4 Simpang Titip. Data collection used a mathematical communication ability essay test. Data were analyzed through quantitative descriptive techniques. The results of the study are a mathematical communication competency score of 64.06 in the Moderate category. In indicator 1) explaining mathematical concepts through writing, demonstrations and representing them visually, the mean score was 63.75, which is a moderate classification. For indicator 2) understanding, interpreting and assessing mathematical ideas in writing and visually, the average was 67.18, which is in the Moderate category. In indicator 3) the use of language or vocabulary and mathematical structures in terms of explaining ideas, representing combinations or making models, the average was 61.25, which is in the moderate category. The implications of the research are that teachers can evaluate students in the form of written mathematical communication competency tests in the form of descriptive story questions. Mathematical communication competency tests through students' daily problems can encourage students to develop their communication competencies.